2005
DOI: 10.1161/01.str.0000166045.12976.af
|View full text |Cite
|
Sign up to set email alerts
|

Silent Myocardial Ischemia in Patients With Symptomatic Intracranial Atherosclerosis

Abstract: Background and Purpose-Optimization of coronary risk evaluation in stroke patients has been encouraged. The relationship between symptomatic intracranial atherosclerosis and occult coronary artery disease (CAD) has not been evaluated sufficiently. We aimed to investigate the prevalence of silent myocardial ischemia in patients with symptomatic intracranial atherosclerosis and to identify factors associated with its presence. Methods-From 186 first-ever transient ischemic attack or ischemic stroke patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 26 publications
1
23
1
4
Order By: Relevance
“…Small studies have suggested that 23-58% of stroke patients without clinical CAD may have asymptomatic myocardial ischemia, as determined by exercise ECG or stress myocardial scintigraphy, [15][16][17][18] but Japanese people are considered to have CAD less frequently than Western people. 19 However, our study showed a similar frequency to other studies of Western populations and although the high incidence may be partially attributed to a CAD definition of ≥50% stenosis, rather than ≥75%, we can say that Japanese patients with cerebral infarction have as high a risk of asymptomatic CAD as Western patients.…”
Section: Discussionmentioning
confidence: 99%
“…Small studies have suggested that 23-58% of stroke patients without clinical CAD may have asymptomatic myocardial ischemia, as determined by exercise ECG or stress myocardial scintigraphy, [15][16][17][18] but Japanese people are considered to have CAD less frequently than Western people. 19 However, our study showed a similar frequency to other studies of Western populations and although the high incidence may be partially attributed to a CAD definition of ≥50% stenosis, rather than ≥75%, we can say that Japanese patients with cerebral infarction have as high a risk of asymptomatic CAD as Western patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our transcranial Doppler, magnetic resonance angiography and CT angiography protocols have been described in detail elsewhere [12]. Intracranial stenosis was defined as a focal narrowing (>50% in luminal reduction) affecting the main cerebral large arteries.…”
Section: Methodsmentioning
confidence: 99%
“…pacientų, sirgusių MI dėl intrakranijinių arterijų stenozės (IAS), buvo stebima sutrikusi miokardo perfuzija [14]. Panašus tyrimas buvo atliktas ir Kioto universitete (Japonija).…”
Section: Koronarine šIrdiesunclassified